Comparison of voluntary food intake and palatability of commercial weight loss diets in healthy dogs and cats. Issue 1 (December 2016) - Hours, Marie; Sagols, Emmanuelle; Junien-Castagna, Ariane; Feugier, Alexandre; Moniot, Delphine; Daniel, Ingrid; Biourge, Vincent; Samuel, Serisier; Queau, Yann; German, Alexander
Abstract Background Obesity in dogs and cats is usually managed by dietary energy restriction using a purpose-formulated weight loss diet, but signs of hunger and begging commonly occur causing poor owner compliance. Altering diet characteristics so as to reduce voluntary food intake (VFI) can improve the likelihood of success, although this should not be at the expense of palatability. The aim of the current study was to compare the VFI and palatibility of novel commercially available canine and feline weight loss diets. Methods The relative performance of two canine (C1 and C2) and two feline (F1 and F2) diets was assessed in groups of healthy adult dogs and cats, respectively. Diets varied in energy, protein, fibre, and fat content. To assess canine VFI, 12 (study 1) and 10 (study 2) dogs were offered food in 4 meals, for 15 min on each occasion, with hourly intervals between the meals. For feline VFI, 12 cats were offered food ad libitum for a period of 18 h per day over 5 consecutive days. The palatability studies used separate panels of 37 dogs and 30 cats, with the two diets being served, side-by-side, in identical bowls. Results In dogs, VFI was significantly less for diet C1 than diet C2 when assessed on energy intake (study 1, 42% less, P = 0.032; study 2, 28% less, P = 0.019), but there was no difference in gram weight intake (study 1:P = 0.964; study 2:P = 0.255). In cats, VFI was 17% less for diet F1 than diet F2 when assessed by energy intake (P < 0.001), but there was again no difference in gram weight (P = 0.207). There was no difference in palatability between the two canine diets (P = 0.490), whilst the panel of cats diet preferred F1 to F2 (P < 0.001). Conclusion Foods with different characteristics can decrease VFI without affecting palatability in both dogs and cats. The effects seen could be due to decreased energy content, decreased fat content, increased fibre content, different fibre source, and increased protein content. Further studies are now needed to determine whether similar findings occur in obese dogs and cats on controlled weight loss programmes.